Validitas Media Pembelajaran E-learning Berbasis Edmodo tentang Materi Genetika - Ardi; Syamsurizal; Fitri Arsih; Novia Erlinda; Reni Alfionora (Universitas Nusantara PGRI Kediri, 2022)
The rapid development of technology and information affect many fields, including education. In field of education, the development of technology and information can be observed in the use of e-learning in learning activities. E-learning is a systems that allows learning activities to occur without being limited by space and time so tha learning activities can be carried out even though teachers and students do not meet face to face. One of the easiest to use e-learning is edmodo. Edmodo is an e-learning platform that has easy acces like the facebook social media platform. Research on edmodo was carried out with the aim of producing valid edmodo learning media. The research was carried out using the Research and Development (R&D) method with 4-D model. Validation is carried out on four main aspect, namely the feasibility of content, language, presentation, and graphics. From the validation process on these four aspects, the validity value is 89,51% with valid category. Therefore, the edmodo learning media that was developed was valid.